Estimates of mortality and population changes in England and Wales over the two World Wars - Evgueni Andreev; Domantas Jasilionis; Vladimir Shkolnikov; Dmitri A. Jdanov (Demographic Research, 2005)
Almost one million soldiers from England and Wales died during the First and Second World War whilst serving in the British Armed Forces. Although many articles and books have been published that commemorate the military efforts of the British Armed Forces, data on the demographic aspects of British army losses remain fragmentary. Official population statistics on England and Wales have provided continuous series on the civilian population, including mortality and fertility over the two war periods. The combatant population and combatant mortality have not been incorporated in the official statistics, which shows large out-migration at the beginning and large in-migration towards the end of the war periods. In order to estimate the dynamics of the total population and its excess mortality, we introduce in this paper a model of population flows and mortality in times of war operations. The model can be applied to a detailed reconstruction of war losses, using various shapes of the input data. This enables us to arrive at detailed estimates of war-related losses in England and Wales during the two world wars. Our results agree with elements of data provided by prior studies.